Upaya Peningkatan Aktivitas Belajar Siswa Melalui Model Pembelajaran Kooperatif Tipe Make A Match - Letriani, Ni Kadek Okta; Tripalupi, Lulup Endah (Universitas Pendidikan Ganesha, 2021)
This study is different from the problems in the twelfth category C OTKP (Otomatisasi Tata Kelola Perkantoran) SMK Negeri 1 Singaraja, whose student learning activities are still relatively low. In order to overcome these problems, the application in type matching of cooperative learning models is studied. The purpose of this study is to determine the increase in learning activities of middle school students in the XII C OTKP SMK Negeri 1 Singaraja category by applying cooperative learning model type matching to the second basic ability of entrepreneurship subjects. This study used the